2004
DOI: 10.1002/ijc.20333
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of growth and survival of human head and neck squamous cell carcinoma cells by curcumin via modulation of nuclear factor‐κB signaling

Abstract: Key words: HNSCC; NF-B; IB␣; IKK; apoptosis; MMP-9; cyclin D1; COX-2Head and neck squamous cell carcinoma (HNSCC) includes epithelial malignancies that arise from the mucosal lining of the oral cavity, oropharynx, nose and pernasal sinuses, hypopharynx and larynx. These cancers occur more than twice as often in men as in women. 1 HNSCC are among the most morbid of human cancers and affect annually nearly 500,000 people world-wide and approximately 40,000 cases in the United States, making it the sixth most com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
173
0
11

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 261 publications
(191 citation statements)
references
References 59 publications
7
173
0
11
Order By: Relevance
“…Furthermore, suppression of TNF cell signaling pathway in HNSCC cells downregulated the constitutively active NF-kB, and proliferation of cells (Figure 8). Using DNA binding and immunocytochemical analysis, we and others have previously shown that NF-kB is constitutively active in HNSCC Aggarwal et al, 2004). Our results, for the first time, now demonstrate that HNSCC cells express transcriptionally active NF-kB.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Furthermore, suppression of TNF cell signaling pathway in HNSCC cells downregulated the constitutively active NF-kB, and proliferation of cells (Figure 8). Using DNA binding and immunocytochemical analysis, we and others have previously shown that NF-kB is constitutively active in HNSCC Aggarwal et al, 2004). Our results, for the first time, now demonstrate that HNSCC cells express transcriptionally active NF-kB.…”
Section: Discussionsupporting
confidence: 71%
“…More recently, constitutively active NF-kB activation has also been found in cancer patients and shown to correlate with prognosis of the disease (Buchholz et al, 2005;Izzo et al, 2006). Work from our laboratory and others have shown that NF-kB is constitutively active in head and neck squamous cell carcinoma (HNSCC) Aggarwal et al, 2004), and play a critical role in the proliferation of the tumor cells LoTempio et al, 2005). Additionally, HNSCC have been shown to produce inflammatory cytokines such as interleukin (IL)-6 and IL-8 which are also regulated by NF-kB (Wolf et al, 2001;Wang et al, 2002;Thomas et al, 2004).…”
Section: Introductionmentioning
confidence: 97%
“…33 Curcumin represents another potential therapeutic option in squamous cell carcinoma of the tonsil by virtue of its ability to inhibit the growth and survival of human head and neck squamous cell carcinoma cells via modulation of NF-kB signaling. 34 The latter is accomplished through curcumin's ability to abrogate I-kB alpha kinase (IKK), which is needed for NF-kB activation. Curcumin is also attractive because of its apparent use and relative pharmacological safety in humans.…”
Section: Discussionmentioning
confidence: 99%
“…In studies of the myeloid cell line ML-1a, Singh and Aggarwal reported that curcumin inhibited IkBa phosphorylation, degradation, and NF-kB translocation induced by a diverse range of stimuli including TNF, hydrogen peroxide, and phorbol esters [2]. Subsequent studies confirmed curcumininduced inhibition of NF-kB translocation in multiple cell types, including colon [3], gastric [4], pancreatic [5], and squamous epithelial tumor cell lines [6] as well as B-cell lymphoma and multiple myeloma cell lines [7,8]. Although the precise mechanism by which NF-kB translocation is inhibited remains unclear, Plummer et al demonstrated that curcumin reduced NF-kB translocation in HEK293 cells transfected with NIK, IKKa, or IKKb kinases [3].…”
Section: Introductionmentioning
confidence: 92%